An Ethnographic Study of Neuro-linguistic Programming : Outcome-based Impacts to EFL Speaking skill - Wattiheluw, Nurlaila; Mahmud, Murni; Abduh, Amirullah (Institut Agama Islam Negeri Palopo, 2024)
Neuro-linguistic Programming (NLP) offers innovative strategies in pedagogy. NLP supports effective communication, personal growth, and transformative learning. This research examined the implementation of neuro-linguistic programming and its impacts on students’ preferred outcome of speaking skills. The data of this research were collected using ethnographic approach through interviews, participatory observation, and document analysis. The research involved twenty five students majoring in the English department at Prof. K.H. Saifuddin Zuhri State Islamic University Purwokerto, central Java, who were attending a speaking course in the 2023/2024 academic year. The implementation of NLP strategies (setting clear learning objectives, building rapport, sensory acuity, and flexibility) positively affected subjects’ speaking skill aspects (fluency, vocabulary mastery, mimicry speaking style and pronunciation, and effective communication) to meet their desired goals except grammar comprehension. However, the strategy did not work effectively on the improvement of grammar comprehension. Therefore, future researchers are encouraged to make improvement in this aspect. Future researchers are also encouraged to analyse the changes in students’ behaviours or attitudes in longitudinal research to further strengthen the findings of this research.